(untitled) (Biological Sciences - PJSIR, 1999)
A method for the production of cellulose acetate from thejute sticks, Corchorus capsularis: late variety -1 (CVL -1), Fulguni Tossa (0-9897), and BJC 718, was described. Alphacelluloses were isolated from thejute sticks by a standard method. The methodof acetylation of thealphacelluloseswasthen standardisedby using acetic anhydride (310%on the dry weight of the material, i.e. alphacellulose,on the weight of material, o.w.m.),glacial acetic acid (410% o.w.m.) and sulphuric acidunder the specifiedconditions.The yieldsofcelluloseacetatewerefoundtobe:CVL-l: 55.80%,0-9897: 45.60% and BJC 718:63.74% on the dry weight basis on the respectivejute sticks. The yields were compared withthe previous results and foundtobe greaterin the presentinvestigation.The degreeof substitution(D.S) foreach of thethree acetates was found to be around two.